Price-Competition Between India, Japan, and the U.K. in the Indian Cotton Textile Market During the Nineteen-Thirties - Mehta, Fredie A. (The Review of Economics and Statistics, 1957)
Fredie A. Mehta, Price-Competition Between India, Japan, and the U.K. in the Indian Cotton Textile Market During the Nineteen-Thirties, The Review of Economics and Statistics, Vol. 39, No. 1 (Feb., 1957), pp. 75-78